Don't be too SMART, but SAVE your goals: Proposal for a renewed goal-setting formula for Generation Y - Christoph Desjardins (Journal of Applied Leadership and Management, 2021)
Research Question: What are the scientific origins of the SMART goal-setting formula? What are the motivational needs of Generation Y? How can the SMART formula be renewed to match the expectations of Generation Y? Methods: Literature review and web research. Conceptual design. Results: The SMART formula was found as an endemic, but non-scientific concept. A major limitation of the SMART acronym is its cognitive focus and framing. Motivational needs of Generation Y are not explicitly considered. Theoretical development of the new goal-setting formula SAVE for Generation Y: Specific, Attainable, Valuable, Elevated.
Keywords: 650